THE ANALYSIS OF THE EFFECT OF PROFITABILITY, LIQUIDITY, AND COMPANY SIZE ON TIMELINESS OF FINANCIAL REPORTING : CASE STUDY OF ENERGY SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Rizky, Sari Fateh; Ratnawati, Dyah (Yayasan Education and Social Center, 2024)
This study aims to determine the effect of profitability, liquidity, and company size on the timeliness of financial reporting of energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2022. The type of research used in this research is a quantitative approach. This research uses secondary data from the annual financial reports of energy sector companies listed on IDX for 2019-2020. The population in this study included all energy sector companies listed on the IDX in the 2019-2022 period. The sampling technique used in this research was purposive sampling, so the sample used was 18 companies. The data analysis used to test the hypothesis is logistic regression with a significance level of 5% and using SPSS version 29. The results of this study indicate that profitability and company size do not affect the timeliness of corporate financial reporting, as evidenced by the significance value > 0.05 in the hypothesis test results. Liquidity is proven to affect the timeliness of corporate financial reporting, with a significance value in the hypothesis test <0.05